LEARNING ENGLISH THROUGH SOCIAL MEDIA - Dewi Suriyani Djamdjuri; Muhammad Furqan; Azkia Aulia Fitra Soedarman (PT. Intelek Cendikiawan Nusantara, 2024)
The purpose of this study is to determine social media users' perspectives on learning English using social media. This study collects data using a qualitative descriptive approach, with questionnaires distributed to 26 social media users who are learning English through social media. The data collected through a set of questionnaires can be summarized as follows: 1) The majority of respondents agreed that their English skills improved as a result of using social media; 2) The majority of respondents agreed that they frequently get new vocabulary from social media; 3) The majority of respondents agreed that they can improve their speaking using the duet feature on social media; and 4) The majority of respondents agreed that they can get English material on social media; 5) The majority of respondents agree they enjoy learning English using social media; 6) The majority of respondent use of social media makes it easier to learn English. Therefore, the use of social media provides benefits for its user to learn English.